Generation of Mature Nα-Terminal Acetylated Thymosin α1 by Cleavage of Recombinant Prothymosin α - Bo Liu; Xin Gong; Shaohong Chang; Peng Sun; Jun Wu (The Scientific World Journal)
Nα-terminal acetylation of peptides plays an important biological role but is rarely observed in prokaryotes. Nα-terminal acetylated thymosin α1 (Tα1), a 28-amino-acid peptide, is an immune modifier that has been used in the clinic to treat hepatitis B and C virus (HBV/HCV) infections. We previously documented Nα-terminal acetylation of recombinant prothymosin α (ProTα) in E. coli. Here we present a method for production of Nα-acetylated Tα1 from recombinant ProTα. The recombinant ProTα was cleaved by human legumain expressed in Pichia pastoris to release Tα1 in vitro. The Nα-acetylated Tα1 peptide was subsequently purified by reverse phase and cation exchange chromatography. Mass spectrometry indicated that the molecular mass of recombinant Nα-acetylated Tα1 was 3108.79 in, which is identical to the mass of Nα-acetylated Tα1 produced by total chemical synthesis. This mass corresponded to the nonacetylated Tα1 mass with a 42 Da increment. The retention time of recombinant Nα-acetylated Tα1 and chemosynthetic Nα-acetylated Tα1 were both 15.4 min in RP-high performance liquid chromatography (HPLC). These data support the use of an E. coli expression system for the production of recombinant human Nα-acetylated Tα1 and also will provide the basis for the preparation of recombinant acetylated peptides in E. coli.